Peran Kepala Sekolah, Guru Dan Tenaga Administrasi Dalam Penjaminan Mutu Madrasah Di Mts Negeri Plupuh Kabupaten Sragen - Susilo, Djoko; , Prof.Dr. Abdul Ngalim,M.M.,M.Hum (2016)
The objectives of the study are to describe: (1) the characteristics of headmaster roles in madrasah quality assurance at MTs Negeri Plupuh, Sragen; (2) the characteristics of teachers roles in madrasah quality assurance at MTs Negeri Plupuh, Sragen, (3) the characteristics of administrative staff roles in madrasah quality assurance at MTs Negeri Plupuh, Sragen. The research is qualitative with ethnography designed. Subjects of the research aremadrasah principal, teachers, and administrative staff at MTs Negeri Plupuh. The technique of gathering data used in this research are in depth interview, participant-observation, and documentation. The techniques of data analysis used in this research are data reduction, data display, and data verification. Data validity is checked usingmethod triangulation and source triangulation, dependability and confirmability. The results show that 1) the headmaster roles in madrasah quality assurance at MTs Negeri Plupuh, Sragen include strengthening school curriculum, strengthening SBM, human resources management, financial management, and school facilities management. 2) The teacher roles in madrasah quality assurance at MTs Negeri Plupuh, Sragen include teacher as controller, observer, organizer, and explainer. The teachers perform include in learning environment planning, teacher resource planning, class administration planning, and learning administration planning. 3) The roles of administrative staff in madrasah quality assurance at MTs Negeri Plupuh, Sragen include creating condusive atmosphere to make professional commitment in assuring education quality. They also include giving optimal service. The co-evaluation include financial evaluation, and facilities evaluation with principal through administrative and managerial supervision. Keywords: headmaster, teacher, administrative staff, quality assurance, madrasah